Effect of 0.01% Atropine on diopter and optic axis in adolescents and children with myopia - Xia, Liping; Zhao, Hongwei; Wang, Yuan (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to investigate the effect of 0.01% Atropine eye drops on diopter and optic axis in adolescents and children with myopia. A total of 164 children with myopia were randomly divided into two groups, Group A and Group B with 82 patients in each group, according to the digital table method. Group A was treated with 0.01% Atropine eye drops, while Group B was treated with single vision lenses. Before the treatment, there was no significant difference in diopter and axial length between the two groups (P=0.624 and P=0.123). After 12 months of treatment, the diopter and axial length of Group A were lower than those of Group B (P < 0.001 and P = 0.005). There were no obvious adverse reactions during corrective therapy in the two groups. —Continue